Increasing level of liquid pig manure reduces Eisenia andrei and Enchytraeus crypticus reproduction in subtropical soils - Segat J.C. (2020)
© 2020, The Author(s).Wastes generated in pig production are widely used as agricultural fertilizers. Nevertheless, such form of disposal supplies large amounts of waste in soils annually and can cause environmental pollution. The ecological risk of this practice to soil organisms has received little attention. Ecotoxicological tests are used to evaluate the toxicity of contaminants added to the soil biota. The aimed to evaluate the effect of liquid pig manure (LPM) on the reproduction of Eisenia andrei and Enchytraeus crypticus when applied in natural soils. LPM doses caused effects on earthworm reproduction in both soils, with EC50 of 112 and 150 m3 ha−1 in the Entisol and Nitosol, respectively. On enchytraeids, LPM had bigger effects, leading to EC50 of 17.7 and 45.0 m3 ha−1 in the Entisol and Nitosol, respectively. The results emphasize the importance to consider the ecological risks of LPM of conducting studies with natural soils and edaphic fauna as indicators.